Comparable effect of tolvaptan in heart failure patients with preserved or reduced ejection fraction - Shunsuke Kiuchi; Shinji Hisatake; Takayuki Kabuki; Takashi Oka; Shintaro Dobashi; Takahiro Fujii; Takanori Ikeda (Clinical and Experimental Hypertension, 2020)
Background: It is unclear that the difference in efficacy of tolvaptan (TLV) on the length of hospital stay for both heart failure (HF) preserved ejection fraction (EF) (HFpEF) and reduced EF (HFrEF) patients. Methods: We investigated 369 patients who were hospitalized with HF from February 2011 to June 2016 and initiated TLV. Patients who died in hospital, transferred hospital or clinical scenario 4 or 5 were excluded. Finally, we analyzed 108 patients with HFpEF and 96 patients with HFrEF. We evaluated the relationship between the length of hospital stay and the date of TLV initiation. Moreover, we compared the early use (within the median) and delayed use (the median or later) of TLV. Results: The date of TLV initiation was statistically associated with the length of hospital stay in both HFpEF and HFrEF (HFpEF: r = 0.625, P < 0.001, HFrEF: r = 0.618, P < 0.001). In HFpEF, the length of hospital stay in delayed use group was significantly longer than the early use group (22.2 ± 10.7 days and 38.1 ± 22.6 days, P < 0.001). The result was similar in HFrEF (22.0 ± 15.0 days and 32.1 ± 22.0 days, P = 0.008). On the other hand, there were no statistically significant differences in the length of hospital stay after initiation of TLV in both HFpEF and HFrEF. Other findings (including the severity of HF) were similar between the early use group and the delayed group in HFpEF and HFrEF. Conclusions: The time until TLV initiation after hospitalization was related to the length of hospital stay in HFpEF and HFrEF patients.